2017
DOI: 10.1016/j.athoracsur.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Cardioscopically Guided Beating Heart Surgery: Paravalvular Leak Repair

Abstract: Purpose There remains a paucity of direct visualization techniques for beating-heart intracardiac procedures. To address this need, we evaluated a novel cardioscope in the context of aortic paravalvular leaks (PVLs) localization and closure. Description A porcine aortic PVL model was created using a custom-made bioprosthetic valve and PVL presence was verified by epicardial echocardiography. Transapical delivery of occlusion devices guided solely by cardioscopy was attempted 13 times in a total of 3 pigs. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…After initial wall-following exploration, blinded animals as well as people have been observed to use their environmental map to create shortcuts through free space (33,34,36,37). While not formally studied, we observed similar behavior in our previously published experiments with a handheld instrument (13). During initial use of the instrument, the clinician navigated from the apex to the aortic annulus using wall following.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…After initial wall-following exploration, blinded animals as well as people have been observed to use their environmental map to create shortcuts through free space (33,34,36,37). While not formally studied, we observed similar behavior in our previously published experiments with a handheld instrument (13). During initial use of the instrument, the clinician navigated from the apex to the aortic annulus using wall following.…”
Section: Discussionsupporting
confidence: 81%
“…To evaluate the autonomous navigation algorithms, we performed in vivo experiments comparing autonomous navigation with teleoperated (i.e., joystick-controlled) robotic navigation. We also compared these two forms of robotic navigation with our results in (13) describing manual navigation of a handheld catheter. In all cases, the only sensing used consisted of the video stream from the tip-mounted endoscope, kinesthetic sensing of the robot / human and force sensing of the human (handheld).…”
Section: Resultsmentioning
confidence: 99%
“…Padala et al [7] reported use of a blunt convex Plexiglass tip that enabled intracardiac tissue visualization in 80-kg porcine models (n = 5) through sternotomy and minithoracotomy incisions. Recently, Rosa et al [8] described cardioscope fitted with a silicone optical window for detecting paravalvular leaks in porcine models (n = 3) through median sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Through miniaturization and seamless catheter connection solutions, as well as improved cardiac perfusion techniques, the development of intracardiac imaging technologies has been significantly facilitated. Various teams report their intracardiac visualization tools and device evaluations with differing criteria for success [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, a method to create a bioprosthetic semilunar valve helped provide research-grade heart valves to independent groups [9]. This device fabrication method was used later in 2017 to simulate a paravalvular leak for repair using cardioscopic imaging [10]. The same method was used in 2019 to test autonomous robotic navigation [11].…”
Section: Introductionmentioning
confidence: 99%